Mathematical modeling of the body's immune response to infectious disease with external factors - Українець, Олег; Бігун, Ярослав (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The article investigates a mathematical model of the immune response to an infectious disease, considering external factors that influence the course of the disease. Stationary solutions and their existing conditions have been identified, along with their medical interpretation and sufficient conditions for asymptotic stability. У статті досліджено математичну модель імунної відповіді на інфекційне захворювання з урахуванням зовнішніх факторів, які впливають на перебіг захворювання. Знайдено стаціонарні розв’язки та умови їх існування, дано їх медичне пояснення, вказано достатні умови асимптотичної стійкості.